Muscular weakness represents the main limiting factor of walk, functional independence and quality of life of myelopathy patients associated to HTLV-1 - Caiafa, Renata Costa; Orsini, Marco; Felicio, Lilian R.; Puccioni-Sohler, Marzia (Arquivos de Neuro-Psiquiatria, 2016)
HTLV-1-associated myelopathy is a progressive disabling disease associated with gait abnormalities.Objective To identify and quantify the main muscles affected by weakness and spasticity, their impact on gait, functional capacity and on quality of life of HTLV-1-associated myelopathy patients.Method We evaluated lower limbs muscular strength according to the Medical Research Council scale, spasticity according to the modified Ashworth scale, daily activities according to the Barthel Index and quality of life according to the Short-Form Health Survey-36 of 26 HTLV-1-associated myelopathy patients.Results The muscles most affected by weakness included the dorsal flexors and knee flexors. Spasticity predominated in the hip adductor muscles and in plantar flexors. Assistance for locomotion, minimal dependence in daily activities, limitations in functional capacity and physical aspects were the most common findings.Conclusion The impairment of gait, functional dependence and quality of life were predominantly a consequence of intense muscle weakness in HTLV-1-associated myelopathy patients.
Keywords: HAM/TSP; functional ability; gait; quality of life